The Hydrological cycle of Greenland and Antartica - Orvig, Svenn (1972)
Includes a bibliography Article dealing with the hydrological cycle of Greenland and the glaciology of the Antarctic Continent - considers water resources of ice caps influencing the world water balance, discusses the stratigraphy of firn and ice, refers to the use of new mathematical models for the study of the energy balance over snow fields